Border security management in the MENA region: models of nascent and ascendant coordination and cooperation. Issue 4 (2nd October 2021) - Meier, Daniel
ABSTRACT: Managing border in the Middle East has to contend with two main challenges: terrorism and migratory flows and movement of labourers who circulate among the Maghreb, Mashreq, Gulf and Europe. This article focuses specifically on the process of integrated border management (IBM): an effort to coordinate border agencies and develop measures of integration pursuant to international mechanisms. How to organize border security management in the Middle East? And what kind of coordination and cooperation currently exists among states? Three cases studies in Libya, Lebanon and Saudi Arabia explore the feasible scenarios as they each refer to a specific form of state (failed, weak and hegemonic).